Transcapillary escape rate and capillary permeability into albumin in patients with Plasmodium falciparum - S. Areekul (2018)
The transcapillary escape rate and capillary permeabiliuty to albumin were studied in five patients with Plasmodium falciparum malaria and six control subjects by using 125 I-HSA. The mean transcapillary escape rate of albumin, calculated from the slope of the plasma disappearance curve of 125 I-HSA, was found to be significantly higher in the malaria patients than in the control group. As the plasma volume increased while the plasma albumin concentration decreased in these patients, this resulted in a significantly higher plasma clearance and outflux of albumin from the intravascular to the extravascular compartments. Both the effective capillary pore area per unit path length available for restricted diffusion and the specific permeability coefficient of the capillary to albumin were found to be grossly elevated in the patients' group. These findings indicate that there was an increased leakage of plasma albumin in patients with P. falciparum malaria as a result of increased capillary surface area and an increased capillary permeability to albumin.